Association study of dopamine receptor genes polymorphisms with the risk of schizophrenia in the Han Chinese population. (30th November 2016) - Yang, Beimeng; Niu, Weibo; Chen, Shiqing; Xu, Fei; Li, Xingwang; Wu, Xi; Cao, Yanfei; Zhang, Rui; Yang, Fengping; Wang, Lu; Li, Weidong; Xu, Yifeng; et al.
Abstract: Schizophrenia is a highly heritable psychiatric disorder often associated with dopamine-related genetic variations. Thus, we performed a case-control study in 1504 Han Chinese population to evaluate the association of DRD1, DRD2 and DRD3 polymorphisms with schizophrenia. No statistically significant difference in allelic or genotypic frequency was found between schizophrenia and control subjects. Strong positive linkage disequilibrium was detected among the SNPs within DRD1 and DRD2. However, no positive haplotype distribution was found to be associated with schizophrenia. Our results indicated that DRD1, DRD2 and DRD3 may not be the susceptibility genes for schizophrenia in the Chinese Han population. Highlights: No statistically significant difference in allelic or genotypic frequency was found in the Han Chinese population. Strong positive linkage disequilibrium was detected among the SNPs within DRD1 and DRD2. No positive haplotype distribution was found to be associated with schizophrenia.